The complete chloroplast genome sequences of three lilies: genome structure, comparative genomic and phylogenetic analyses - Li, Y.; Zhang, L.; Wang, T.; Zhang, C.; Wang, R.; Zhang, D.; Wu, X.
We sequenced and analyzed the complete chloroplast genomes of Lilium amoenum, Lilium souliei, and Nomocharis forrestii in detail, including the first sequence and structural comparison of Nomocharis forrestii. We found that the lengths and nucleotide composition of the three chloroplast genes showed little variation. The chloroplast genomes of the three Lilium species contain 87 protein coding genes (PCGs), 38 tRNAs, and 8 rRNA genes. The only difference is that Nomocharis forrestii had an additional infA pseudogene. In the sequence analysis of the Lilium chloroplast genomes, 216 SSRs, 143 pairs of long repeats, 571 SNPs, and 202 indels were detected. In addition, we identified seven hypervariable regions that can be used as potential molecular markers and DNA barcodes of Lilium through complete sequence alignment. The phylogenetic tree was constructed from the three chloroplast genome sequences of Lilium obtained here and 40 chloroplast genome sequences from the NCBI database (including 35 Lilium species, 4 Fritillaria species, and one species of Smilax). The analysis showed that the species clustering of the genus Lilium essentially conformed to the classical morphological classification system of Comber, but differences in the classification of individual species remained. In our report, we support the reclassification of Lilium henryi and Lilium rosthorniiy in the genus Lilium. In general, this study not only provides genome data for three Lilium species, but also provides a comparative analysis of the Lilium chloroplast genomes. These advances will help to identify Lilium species, clarify the phylogenetic analysis of the Lilium genus, and help to solve and improve the disputes and deficiencies in the traditional morphological classification.
Keywords: CHLOROPLAST GENOMES; LILIUM; PHYLOGENETIC ANALYSIS